(untitled) (Eastern Journal of Medical Sciences, 2017)
Infectious gastroenteritis can lead to exacerbations of inflammatory bowel disease (IBD) such as ulcerative colitis, which warrants appropriate and timely control with the initiation of specific antibacterial therapy. Herein, we discuss a patient who had presented with an exacerbation of ulcerative colitis due to an infectious gastroenteritis caused by Edwardsiella tarda and had responded to the appropriate antibacterial therapy. This study outlines the importance of a culture of stool samples in all cases of IBD with acute exacerbations.